Financial Technology and Human Resource Competency in Financial Management for UMKM at Palopo City - A. Wulan Lestari; Antong Antong; Halim Usman (JINAV: Journal of Information and Visualization, 2022)
Abstract This study aint to determine the effect of fintech and human resource competencies in the financial management of umkm in palopo city. The data source in this study is primary data. The primary data used in this study were obtained from distributing questionnaires. The population selected for this study were UMKM in Palopo City. Respondents were given a number of statements and then asked to respond with their own statements. Furthermore, respondents were asked to fill out the questionnaire using an anonymous system. This approach aims to avoid potential bias during the data collection process. The research method used is quantitative method and analyzed using Structural Equation Model (SEM) approach using AMOS software. The questionnaire in this study was prepared based on the variables to be tested, namely Financial Technology, Resources, Financial Management of UMKM. All variables are measured using a Liket scale with 5 (five) alternative answers. The following are the specifications: 1) Strongly Disagree; 2) Disagree; 3) Neutral; 4) Agree; 5) Strongly Agree. The results showed that (1) The results of data analysis show that human resource competencies affect financial technology. (2) The results showed that simultaneously the umkm financial management variable had a significant influence on financial technology. (3) While the results of umkm financial management variables have an effect on human resource competencies. Keywords: Fintech, Finance, Human Resources, Management, UMKM